THE ROLE OF FORENSIC ACCOUNTING IN THE DETECTION AND FRAUD PREVENTION: A SYSTEMATIC LITERATURE REVIEW - Totok Dewayanto (STIE Pelita Nusantara Semarang, 2023)
This paper presents a systematic literature review (SLR) conducted using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) method to identify and assess existing literature on forensic accounting. The aim is to determine the contribution of forensic accounting to fraud detection and prevention, and to investigate the standard techniques for fraud detection and prevention, as well as the significant challenges that hinder the application of forensic accounting in fraud prevention and detection.The findings of the review reveal a positive correlation between forensic accounting and fraud detection and prevention, with the complexity of fraud being highlighted as a significant factor to consider. The study also emphasizes the need for increased consumer understanding of basic forensic accounting techniques, as well as incorporating forensic accounting into undergraduate and post-graduate courses. The paper's originality and value lie in its holistic approach to addressing fraud detection, prevention, and challenges in forensic accounting, and the use of PRISMA and SLR techniques, which have been under utilized in this field